Psychosocial effects of self-disclosure among Chinese international students in Japan: Focusing on disclosure media and its targets - Gao, Xingjian; Takai, Jiro (Journal of International Students, 2023)
This study examined the effects of four types of self-disclosure on the life satisfaction of Chinese international students studying in Japan. Using an online survey, the study found that offline self-disclosure predicted life satisfaction both directly and indirectly, mediated by received social support and perceived social support, while the direct effect of online self-disclosure was not significant. All four types of self-disclosures predicted received social support, while the social support obtained from host nationals online did not affect perceived support. The analysis also revealed that the paths were moderated by the length of residence in Japan. Only online self-disclosure positively and directly predicted life satisfaction for newcomers, while only offline self-disclosure did for those who had stayed longer. Offline received social support was perceived as helpful for both groups, while that of online predicted perceived social support only for newcomers. Theoretical implications and limitations were discussed.